Refuge recovery : a Buddhist path to recovering from addiction - Levine, Noah (HarperOne, 2014)
Bestselling author and renowned Buddhist teacher Noah Levine adapts the Buddha's Four Noble Truths and Eight Fold Path into a proven and systematic approach to recovery from alcohol and drug addiction--an indispensable alternative to the 12-step program. While many desperately need the help of the 12-step recovery program, the traditional AA model's focus on an external higher power can alienate people who don't connect with its religious tenets. Refuge Recovery is a systematic method based on Buddhist principles, which integrates scientific, non-theistic, and psychological insight. Viewing addiction as cravings in the mind and body, Levine shows how a path of meditative awareness can alleviate those desires and ease suffering. Refuge Recovery includes daily meditation practices, written investigations that explore the causes and conditions of our addictions, and advice and inspiration for finding or creating a community to help you heal and awaken. Practical yet compassionate, Levine's successful Refuge Recovery system is designed for anyone interested in a non-theistic approach to recovery and requires no previous experience or knowledge of Buddhism or meditation.